Providers’ perspective on vaginal birth after cesarean birth: a qualitative systematic review - Antita Kanjanakaew; Atchareya Jiramanee; Manassawee Srimoragot (BMC Pregnancy and Childbirth)
Abstract Background Vaginal Birth after Cesarean Birth (VBAC) is a birth mode recommended for reducing repeat cesarean which potentially contributes to adverse outcomes. However, VBAC is not normally practiced in some countries. Providers are an important part of the decision-making process on modes of birth among pregnant individuals. Providers’ perspective on VBAC can influence whether they support or avoid conducting VBAC. This review aimed to explore providers’ perspective on VBAC. Methods The comprehensive search was conducted from six databases including PubMed, MEDLINE, Scopus, Cochrane Library, EMBASE, and Google scholar. The studies published in English between 2013 and 2023 were review. The Medical Subject Heading terms for VBAC and perspective were used to search. The eligible studies were selected by the PRISMA flow chart. The initial search yielded 558 articles. After excluding duplicates, articles not retrieved for full-text, and not meeting inclusion and exclusion criteria, eight articles were recruited. Quality appraisal of the studies was performed by the tool of the Joanna Briggs Institute. The meta-aggregation approach was applied to synthesize the findings. Results Eight qualitative articles were included in this review, and six themes were developed including (1) different recognition of VBAC, (2) differences of willingness level of conducting Trial of Labor after Cesarean (TOLAC) (the approach attempting to have VBAC), (3) skills and resources needed when performing TOLAC, (4) protocol for recruiting candidacy and TOLAC management, (5) final decision making on VBAC, and (6) onset and duration of providing TOLAC information. Conclusion Providers play an important role in influencing individuals’ decision on modes of birth. Providers’ positive recognition and willingness of conducting TOLAC potentially impact successful VBAC rate. However, the lawsuit caused by adverse outcomes from TOLAC/VBAC is a main reason for choosing repeat cesarean. Trial registration PROSPERO registration number of this systematic review: CRD42023427662.